Genetic and physiological traits conferring tolerance to ocean acidification in mesophotic corals - Scucchia, Federica; Malik, Assaf; Putnam, Hollie M.; Mass, Tali (Global Change Biology, 2021)
The integrity of coral reefs worldwide is jeopardized by ocean acidification (OA). Most studies conducted so far have focused on the vulnerability to OA of corals inhabiting shallow reefs while nothing is currently known about the response of mesophotic scleractinian corals. In this study, we assessed the susceptibility to OA of corals, together with their algal partners, inhabiting a wide depth range. We exposed fragments of the depth generalist coral Stylophora pistillata collected from either 5 or 45 m to simulated future OA conditions, and assessed key molecular, physiological and photosynthetic processes influenced by the lowered pH. Our comparative analysis reveals that mesophotic and shallow S. pistillata corals are genetically distinct and possess different symbiont types. Under the exposure to acidification conditions, we observed a 50% drop of metabolic rate in shallow corals, whereas mesophotic corals were able to maintain unaltered metabolic rates. Overall, our gene expression and physiological analyses show that mesophotic corals possess a greater capacity to cope with the effects of OA compared to their shallow counterparts. Such capability stems from physiological characteristics (i.e., biomass and lipids energetics), a greater capacity to regulate cellular acid–base parameters, and a higher baseline expression of cell adhesion and extracellular matrix genes. Moreover, our gene expression analysis suggests that the enhanced symbiont photochemical efficiency under high pCO2 levels could prevent acidosis of the host cells and it could support a greater translocation of photosynthates, increasing the energy pool available to the host. With this work, we provide new insights on the response to OA of corals living at mesophotic depths. Our investigation discloses key genetic and physiological traits underlying the potential for corals to cope with future OA conditions.